Top-Down Protein Identification of Proteasome Proteins with nanoLC FT-ICR MS Employing Data-Independent Fragmentation Methods - Lakshmanan, Rajeswari (2014)
A comparison of different data-independent fragmentation methods combined with liquid chromatography (LC) coupled to high resolution Fourier-transform ion cyclotron resonance (FT-ICR) tandem mass spectrometry (MS) is presented for top-down MS of protein mixtures. Proteins composing the 20S and 19S proteasome complex and their post-translational modifications were identified using a 15-Tesla FT-ICR mass spectrometer. The data-independent fragmentation modes with LC timescales allowed for higher duty cycle measurements that better suit on-line LC-FT-ICR-MS. Protein top-down dissociation was effected by funnel-skimmer collisionally activated dissociation (FS-CAD) and CASI (Continuous Accumulation of Selected Ions)-CAD. The N-terminus for 9 out of the 14 20S proteasome proteins were found to be modified, and the α3 protein was found to be phosphorylated; these results are consistent with previous reports. Mass measurement accuracy with the LC-FT-ICR system for the 20–30 kDa 20S proteasome proteins was 1 ppm. The intact mass of the 100 kDa Rpn1 subunit from the 19S proteasome complex regulatory particle was measured with a deviation of 17 ppm. The CASI-CAD technique is a complementary tool for intact protein fragmentation and is an effective addition to the growing inventory of dissociation methods which are compatible with on-line protein separation coupled to FT-ICR MS.